Decade-long changes in spatial mismatch in Beijing, China: Are disadvantaged populations better or worse off?. (June 2018) - Qi, Yunlei; Fan, Yingling; Sun, Tieshan; Hu, Lingqian (Ivy)
Although recent studies have extended the U.S.-centered spatial mismatch hypothesis to Chinese cities, few have examined spatial mismatch conditions over time in Chinese Cities. This research responds to the knowledge gap by using longitudinal data to examine changes in the patterns and magnitudes of spatial mismatch between the 2000s and 2010s in Beijing, China. The longitudinal examination uniquely focuses on spatial mismatch between population and transit-accessible jobs, as opposed to spatial mismatch between population and any jobs. Results show that spatial mismatch conditions worsened among all population groups in the past decade in Beijing, China. When comparing across population groups, spatial mismatch worsened to a much higher degree among disadvantaged groups including the migrant population without local hukou and the low-educated population without college education. Further analyses show that changes in population distribution were primarily responsible for the worsened spatial mismatch conditions. Changes in job distribution and transit networks had limited impacts. Policy recommendations to mitigate spatial mismatch in Beijing include reconfiguration of transit networks and promotion of affordable housing development in transit- and/or job-rich areas.